Mathematical model for the prediction of chip serration frequency in end milling of steel AISI1020 - Patwari, Muhammed Anayet Ullah; Amin, A. K. M. Nurul; Faris, Waleed Fekry (Annals of Faculty of Engineering Hunedoara Romania, 2009)
The present paper discusses the development of a mathematical model based on statistical analysis for predicting the chip serration frequency in end-milling operation of steel AISI1020 using coated TiN insert under dry conditions and full immersion cutting. A small CCD with 2 blocks and 5 replication of centre point in each factorial block was selected to design the experiments and each of the independent variables is considered up-to 5(five) levels in developing the chip serration models in terms of primary cutting parameters (Cutting Speed, Feed, Axial Depth of Cut). The experimental results indicate that the proposed mathematical models could adequately describe the performance indicators within the limits of the factors that are being investigated. The adequacy of the predictive model was verified using ANOVA at 95% confidence level.